2011
DOI: 10.1097/mlr.0b013e31820192cd
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay per Quality-Adjusted Life Year: Is One Threshold Enough for Decision-Making?

Abstract: Preference elicitation methods are acceptable and feasible in the socio-cultural context of an Asian environment and the calculation of WTP/QALY ratio produced meaningful answers. The necessity of considering the QALY type or disease-specific QALY in estimating WTP/QALY ratio was highlighted and 1 to 3 times of gross domestic product/capita recommended by World Health Organization could potentially serve as a benchmark for threshold in this Asian context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
5
22

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 14 publications
(20 reference statements)
4
53
5
22
Order By: Relevance
“…With cost-effectiveness/cost-utility analysis increasingly being adopted by various jurisdictions, quantifying the threshold of cost-effectiveness analysis would offer a benchmark for interpreting economic evaluation. Using the stated preference data to quantify the WTP/QALY has been explored previously by our study group, and this elicitation method for WTP/QALY ratio was found to be acceptable and feasible, as well as produce meaningful answers among Chinese subjects [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With cost-effectiveness/cost-utility analysis increasingly being adopted by various jurisdictions, quantifying the threshold of cost-effectiveness analysis would offer a benchmark for interpreting economic evaluation. Using the stated preference data to quantify the WTP/QALY has been explored previously by our study group, and this elicitation method for WTP/QALY ratio was found to be acceptable and feasible, as well as produce meaningful answers among Chinese subjects [20].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a WTP/QALY threshold study was conducted recently in China by Zhao et al [20] on patients with chronic prostatitis by measuring the utility (measured by the EQ-5D and the six-dimensional health state short form [derived from SF-36]) and the WTP simultaneously. In that study, based on the indirect preference elicitation method (using the EQ-5D and the six-dimensional health state short form [derived from SF-36]), the WTP/QALY value was successfully elicited for both chronic prostatitis and general populations, with a higher WTP/QALY value in the chronic prostatitis group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The World Health Organization (WHO) cites an even more generalizable range of 1 to 3 times a nation's gross domestic product per capita as the willingness to pay for one QALY gained. 17 Taking this into consideration, to make appropriate and fair decisions regarding investment in new health care innovations, it is important that the ICER be established through rigorous study and that those responsible for resource allocation are transparent in their decisions regarding willingness to pay. Fig.…”
Section: Willingness-to-pay Threshold In Current Practicementioning
confidence: 99%
“…We used three times the per capita gross domestic product (GDP) of China in 2013 ($US19,887)/QALY as the cost-effective threshold according to WHO recommendations [36][37][38]. This recommendation has shown potential for serving as a benchmark for thresholds in the Asian context [39]. The R-software environment (version 2.15.2; R Development Core Team, Vienna, Austria) was used for model building, data handling, figure generating, and statistical and output analyses.…”
Section: Sensitivity Analysesmentioning
confidence: 99%